The Motif of National Freedom and Person’s Inner Freedom in Lina Kostenko’s Novel «Berestechko» - Гноєва, Ніна Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article investigates one the leading motifs of Lina Kostenko’s historical novel in verse «Berestechko» – the motif of national freedom and person’s inner freedom. It analyses the way in which the causes of the defeat in the battle of Berestechko, the consequences and lessons of that defeat, important historical-philosophic problems are shed light upon through the inner monologue of the main character Bogdan Khmelnytskyi. The dynamics of the hetman’s inner life are shown – from the pain, despair after the defeat to the realisation of its lessons and «the letter of freedom». His reflections on the complexity of Ukrainian people’s struggle for freedom are characterised. It is underlined that they are projected by the author not only to the past but also to the future – to modern times. Attention is paid to the interconnection of the personal and historical plotlines, to the psychologically convincing description of the dramaof the commander, politician, personality. The depth of Lina Kostenko’s comprehension of the Ukrainian mentality is revealed, in particular the slave complex, disbelief in the victory. The polyphonism of the historical novel is pointed out.